Regulatory Policy: Bibliometric Analysis Using the VOSviewer Program - Zhavoronok, А.; Chub, А.; Yakushko, I.; Kotelevets, D.; Lozychenko, O.; Kupchyshynа, O. (International Journal of Computer Science and Network Security, 2022)
Today the regulation of socio-economic development has been the subject of active scientific debate. The modern paradigm of regulatory policy in foreign countries involves a change in the role and strategy of the state, which determines the relevance of this topic. The aim of the article is to study the current state of regulatory policy research. The article is based on a bibliographic analysis of the study of regulatory policy. The study is based on the data search functions of the Scopus platform. It uses a set of VOSviewer program, online visualization of keywords in the titles of scientific journals and citations of publications. The study led to the conclusion that the number of publications that directly study the nature and features of regulatory policy is insignificant, but constantly growing. In our opinion, further research should determine the essence of regulatory policy as a separate category, a description of its features and factors of formation. It is also necessary to develop a common concept that governments should be actively involved in ensuring the quality of regulation, rather than responding to the shortcomings of regulation, which is evolving into regulatory governance
Keywords: regulation, regulatory policy, bibliometric, VOSviewer program.